2013
DOI: 10.1038/ijir.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Association of ED with chronic periodontal disease

Abstract: To examine the relationship between chronic periodontal disease (CPD) and erectile dysfunction (ED), the interview sheet including the CPD self-checklist (CPD score) and the 5-item version of the International Index of Erectile Function (IIEF-5) was distributed to 300 adult men who received a comprehensive dental examination. Statistical analyses were performed by the Spearman's rank correlation coefficient and other methods. Statistical significance was accepted at the level of P<0.05. The interview sheets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 16 publications
3
47
0
Order By: Relevance
“…These primary studies Keller et al, 2012; J. H. Lee et al, 2015;Matsumoto et al, 2014;Oguz et al, 2013;Sharma et al, 2011;Tsao et al, 2015;Uppal et al, 2014;Zadik et al, 2009) were conducted in the following countries: India, Israel, Japan, Korea, Taiwan, and Turkey. Seven studies (Keller et al, 2012;J.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…These primary studies Keller et al, 2012; J. H. Lee et al, 2015;Matsumoto et al, 2014;Oguz et al, 2013;Sharma et al, 2011;Tsao et al, 2015;Uppal et al, 2014;Zadik et al, 2009) were conducted in the following countries: India, Israel, Japan, Korea, Taiwan, and Turkey. Seven studies (Keller et al, 2012;J.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…All studies Keller et al, 2012; J. H. Lee et al, 2015;Matsumoto et al, 2014;Oguz et al, 2013;Sharma et al, 2011;Tsao et al, 2015;Uppal et al, 2014;Zadik et al, 2009) were performed on humans and under health care or university settings. These primary studies Keller et al, 2012; J. H. Lee et al, 2015;Matsumoto et al, 2014;Oguz et al, 2013;Sharma et al, 2011;Tsao et al, 2015;Uppal et al, 2014;Zadik et al, 2009) were conducted in the following countries: India, Israel, Japan, Korea, Taiwan, and Turkey.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study was aimed for investigating the association of CP with the erectile dysfunction (ED) that also supports that CP had a high association with ED in young adults at 30-40 years [5]. Additional independent clinical trial also suggested that dental health is important as a preventive medicine for ED [6].…”
Section: Oral Biologymentioning
confidence: 99%